Finite Element Analysis of the Stress Changes Associated With the Growth of Acne Keloids - Nobuaki Ishii, MD; Satoshi Akaishi, MD, PhD; Masataka Akimoto, MD, PhD; Shizuko Ichinose, PhD; Satoshi Usami, PhD; Teruyuki Dohi, MD, PhD; Rei Ogawa, MD, PhD, FACS (Plastic and Reconstructive Surgery, Global Open)
Background:. Almost half of all spontaneously occurring keloids are acne keloids on the anterior chest. These keloids often grow in a crab-claw shape due to predominant tractional stresses on the scar; such stresses are risk factors for keloid growth/progression. To understand the relationship between acne keloid growth and mechanical stress, we conducted finite element analysis (FEA), measured the long/short dimensions of photographed acne keloids, and subjected acne keloids to microscopy. Methods:. FEA was conducted on 10 identically shaped ellipsoidal keloids whose long-axis length rose from 5 to 50 mm in 5-mm increments. They were embedded in the skin and subjected to traction. The stress on the keloid and its surrounding tissues was determined. Dimensions of 220 acne keloids were measured. Electron/light microscopy was conducted on the center, margins, and surrounding tissues of chest acne keloids. Results:. FEA showed that as the keloid “grew,” the tractional stress centered on its core, then became evenly distributed, and then focused increasingly on the tractioned keloid margin, especially its shallow dermis. This is associated with increasing stress in the surrounding tissues at the keloid margin. Clinical dimension measurements showed that acne keloids remained round until 4–5 mm, after which they elongated rapidly. Electron microscopy showed that in the surrounding skin, fragments of keratinocyte, fibrin, and numerous cell fragments were observed just below the epidermal basement membrane. Conclusions:. Keloid-prone acne should be treated with steroid tape or other keloid therapy when it reaches 4–5 mm in diameter.